The biosynthesis of β-lactams - Goh, K; Kee Chuan Goh (1993)
﻿ This thesis reports the work done on two research projects which were carried out independently of each other but converge on the central theme of β-lactam biosynthesis. Chapter 1 provides an overview of biosynthesis in secondary metabolism, with special emphasis on current knowledge about the β-lactams. The first project, covered from Chapters 2 to 5, was part of our group's continuing effort to understand the structure and mechanism of Ring Expandase-Hydroxylase (REXH), an enzyme involved in the biosynthesis of cephalosporin C in Cephalosporium acremonium. REXH is a bifunctional enzyme, converting penicillin N to DAOC and thence to DAC. [diagram omitted from transcription] Chapter 3 discusses the investigation of purification protocols for native REXH and soluble recombinant REXH, as well as an improved refolding method for recombinant REXH expressed as inclusion bodies. Chapter 4 describes two new alternative substrates for REXH, viz. carba-DAOC and DAC, whilst the y-lactam analogue of penicillin N was not found to be a substrate for REXH. Chapter 5 summarises some structural investigations of REXH employing methods such as electrospray mass spectrometry, selective proteolysis and inhibition kinetics. [diagram omitted from transcription] The second project, covered from Chapters 6 to 9, represents the first biosynthetic studies on valclavam, an antifungal produced by Streptomyces antibioticus. Valclavam belongs to the family of clavams which includes clavulanic acid as its most well studied member. [diagram omitted from transcription] Chapter 7 details the development of methods for the bioassay, fermentation and isolation of valclavam. It also describes the isolation of a stable degradation fragment of valclavam which led to the revision of the structures of valclavam and Tü 1718B (another metabolite from the same organism). Chapter 8 gives an account of the whole-cell feeding experiments which strongly suggest that the primary metabolic precursors for valclavam are L-valine, L-arginine, L-methionine and glycerol. Chapter 9 reports the discovery of two enzymic activities, belonging to those of clavaminic acid synthase and proclavaminic acid amidino hydrolase, which are likely to be involved in the biosynthesis of valclavam. Together, the results of Chapters 8 and 9 point to an extensive overlap between the clavulanic acid pathway in Streptomyces clavuligerus and the valclavam pathway in Streptomyces antibioticus.